Knockout of the Aldehyde Dehydrogenase Gene in Fusarium oxysporum for Enhanced Ethanol Yield - Jinxia Fan; Xiaomei Huang; Guoxiang Zheng; Changyu Liu; Ming Wang; Yong Sun; Qian Yang (Energies, 2022)
Acetic acid is the primary by-product generated from ethanol production by Fusarium oxysporum using glucose or xylose as a substrate. Aldehyde dehydrogenase (ALDH) is the critical enzyme in acetic acid metabolism. To decrease acetic acid yield in ethanol production, the 1509 bp DNA of aldh, encoding a 502 amino acid protein with a calculated molecular mass of 54.33 kDa and an isoelectric point of 6.21, was cloned from F. oxysporum. Sequence analysis confirmed that the screened proteins belonged to the ALDH family. A knockout vector, ∆aldh, containing positive (hygromycin resistance gene) and negative (thymidine kinase gene from the herpes simplex virus) selectable markers, was constructed. Ethanol production by the mutant (cs28pCAM-Pstal-∆aldh) in glucose- and xylose-containing media was 0.46 and 0.39 g/g, respectively, and these yields were 16.93% and 34.63% higher than those by the wild-type strain (0.393 and 0.289 g/g). Furthermore, the acetic acid yield of the mutant was 3.50 and 3.01 g/L, respectively, showing a 23.10% and 39.55% decrease compared with the wild-type strain (4.308 and 4.196 g/L). The biomass of the mutant (4.05 and 4.52 g/L) was lower than that of the wild-type strain (4.71 and 5.97 g/L). These results demonstrated the potential use of the genetically stable mutant for industrial bioethanol production.